Смарт-спеціалізація промислових регіонів України: організаційно-економічний супровід - Pidorycheva, Iryna Yu.; Bash, Antonina S. (Institute of Industrial Economics of NAS of Ukraine, 2024)
Industrial regions of Ukraine, especially near-front territories (Donetsk, Luhansk, Kharkiv and Zaporizhzhia regions), suffered the greatest damage and losses as a result of the full-scale war. The needs for their recovery, according to the joint assessment of international institutions and the Ukrainian government, constitute half (50.46% or $207.2 billion USD) of the reconstruction needs for Ukraine. Considering the structural lag of the economy in industrial regions, dominated by sectors with weak innovation activity and low technological intensity, the continuation of pre-war development trajectories is absolutely unacceptable and non-competitive in the context of the Industry 4.0-5.0 which gains traction globally. In the conditions of a significant change in the profiles of industrial regions due to the war, there is an opportunity to revive their economy but on fundamentally new, innovative principles. Smart specialization can be utilized for this purpose, aiming at the structural transformation of the economy and the development of new competitive advantages for regions and countries. Emphasis is placed on the necessity of conducting a critical analysis and rethinking the implementation directions of smart specialization in the industrial regions of Ukraine. This is due to the varying degrees of consideration of its fundamental principles in the regional development strategies for 2021-2027 and the need for the structural transformation of their economies to overcome the consequences of the war for the local population.The purpose of the article is to identify key problems in the field of organizational and economic support for the implementation of the smart specialization approach in the industrial regions of Ukraine and to determine ways to solve them, taking into account purely Ukrainian challenges and EU experience.The role of organizational and economic support for the implementation of the smart specialization approach in national conditions has been substantiated. The scientific understanding of the main organizational and economic problems and shortcomings of the implementation of the smart specialization approach in the industrial regions of Ukraine has been deepened. It is highlighted that freezing these problems and the absence of appropriate actions to address them will prevent structural and innovation transformations in the economies of regions based on the principles of sustainable development, thereby excluding the possibility of overcoming their structural backwardness. Proposals on ways to solve existing organizational and economic problems are substantiated, taking into account purely Ukrainian challenges, and the knowledge obtained in the EU member states during the implementation of this approach over the last ten years. The practical implementation of these proposals will make it possible to adjust the smart-oriented goals and sectoral focuses of regional development strategies, to direct them to the transformation of the economy of industrial regions through the support of sectors and industries that have the potential to develop new competitive advantages.